Histopathological Examination of an Explanted Heart in a Long-Term Responder to Cardiac Stereotactic Body Radiotherapy (STereotactic Arrhythmia Radioablation) - Miszczyk, Marcin; Sajdok, Mateusz; Nożyński, Jerzy; Cybulska, Magdalena; Bednarek, Jacek; Jadczyk, Tomasz; Latusek, Tomasz; Kurzelowski, Radoslaw; Dolla, Łukasz; Wojakowski, Wojciech; Dyla, Agnieszka; Zembala, Michał; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cardiac stereotactic body radiotherapy is an emerging treatment method for recurrent ventricular tachycardia refractory to invasive treatment methods. The single-fraction delivery of 25 Gy was assumed to produce fibrosis, similar to a post-radiofrequency ablation scar. However, the dynamics of clinical response and recent preclinical findings suggest a possible different mechanism. The data on histopathological presentation of post-radiotherapy hearts is scarce, and the authors provide significantly different conclusions. In this article, we present unique data on histopathological examination of a heart explanted from a patient who had a persistent anti-arrhythmic response that lasted almost a year, until a heart failure exacerbation caused a necessity of a heart transplant. Despite a complete treatment response, there was no homogenous transmural fibrosis in the irradiated region, and the overall presentation of the heart was similar to other transplanted hearts of patients with advanced heart failure. In conclusion, our findings support the theorem of functional changes as a source of the anti-arrhythmic mechanism of radiotherapy and show that durable treatment response can be achieved in absence of transmural fibrosis of the irradiated myocardium.